Algorithm of face recognition by principal component analysis - Al-Khateeb, Khalid A. Saeed; Yeop Johari, Jaiz Anuar (IIUM Press, 2002)
A face recognition algorithm based on Principal Component Analysis (PCA) has been developed and tested for computer vision applications. A database of about 400 facial images was used to test the algorithm. Each image is represented by a matrix (112x 92). The database is divided into subsets, where each subset represents one of 10 different individuals. A 96% rate of successful detection and a 90% rate of successful recognition were obtained. Several factors had to be standardized to provide a constrained environment in order to reduce error. The analysis is based on a set of eigenvectors that defines an Eigen Face (EF). The method proved to be simple and effective. The simplified algorithm and techniques expected the process without seriously compromising the accuracy.